Effectiveness of Transcranial direct Current Stimulation on Reaction Time and Performance of Elite Soccer Players - Mahdi Mollazadeh; Hassan Gharayagh Zandi; Mahbobeh Ghayour; Ali Mogaddam (University of Tehran, 2023)
Introduction: The present study aimed to investigate the effect of the transcranial direct current stimulation of the motor cortex on the reaction time and performance of skilled soccer players.Methods: The current study was a quasi-experimental study with a pre-test and a post-test design. The statistical population of this research was the skilled male soccer players of Tehran province in 1401, 36 of whom were selected through convenience sampling and randomly divided into three Primary Motor Cortex Stimulation (N=12), Sham Stimulation (N=12) and Control (N=12) groups. For the primary motor cortex stimulation during transcranial direct current stimulation intervention, the anode electrode was placed at the C3, and the cathode electrode was placed at Fp2. To check and analyze the research hypotheses, the dependent t and the analysis of covariance (ANCOVA) tests with Bonferroni posthoc test were used via SPSS version 22 software.Results: The results showed that in the Motor Cortex tDCS group, the average reaction time after electrical stimulation decreased from 354.25 ± 71.58 to 256.41 ± 63.72 milliseconds, and the average performance increased from 46.00 ± 6.14 to 5.83 ± 68.41. So, according to the significance level of 0.05, a significant difference was observed in reaction time and performance (P <0.05).Conclusion: The results showed that the electrical stimulation of the primary motor cortex affects the reaction time and the performance of skilled soccer players. Since the current research was conducted on skilled soccer players, it is suggested to be as cautious as possible in generalizing the results of this research to novice soccer players and athletes.